2020
DOI: 10.1039/d0fo02144j
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots from roasted chicken accumulate in lysosomes and induce lysosome-dependent cell death

Abstract: Thermal processing may generate toxicant. The carbon dots (CDs) from baked food have toxicity to cells, however, the molecular mechanism remains to be unexplored. The present study investigated the effects...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…With the prolongation of roasting time, CDs were formed nucleation through polymerization (Song, Wu, et al., 2019). A broad peak centered at around 23° was observed in XRD spectra (Figure S1), indicating the amorphous nature of CDs (Wu et al., 2020).…”
Section: Resultsmentioning
confidence: 98%
“…With the prolongation of roasting time, CDs were formed nucleation through polymerization (Song, Wu, et al., 2019). A broad peak centered at around 23° was observed in XRD spectra (Figure S1), indicating the amorphous nature of CDs (Wu et al., 2020).…”
Section: Resultsmentioning
confidence: 98%
“…The isolation of CDs from processed animal derivatives began with char from overcooked barbeque beef. 148 Subsequently, CDs were extracted from roasted hamburger, 149 grilled/roasted pike eel, 150,151 baked lamb, 152–154 roasted duck, 155,156 roasted chicken/chicken breast, 157–160 roasted mackerel fish, 161,162 roasted salmon fish, 163 roasted pork, 164 and roasted beef. 165 Among them, the excellent QYs of the roasted pike eel-derived N-CDs (68.7% and 80.16%) were remarkable, which were attributed to the abundant N-doping (15.91 and 16.39 atomic%, respectively) and surface-passivated amine-linkage or stable excited states.…”
Section: Developments In the Precursors And Synthetic Methods For Ani...mentioning
confidence: 99%
“…165 Among them, the excellent QYs of the roasted pike eel-derived N-CDs (68.7% and 80.16%) were remarkable, which were attributed to the abundant N-doping (15.91 and 16.39 atomic%, respectively) and surface-passivated amine-linkage or stable excited states. 150,151 It was observed that the roasting/baking temperature 149,151,153,156,158,159,164 or baking time 154 had a profound impact on the structure–property relationship of the derived CDs. For example, N-CDs derived from roasted duck showed an increase in absolute QY of 10.53% (200 °C), 13.80% (250 °C), and 38.05% (300 °C) with an increase in the roasting temperature, which was ascribed to the increase in N contents in the N-CDs of 7.18%, 8.70%, and 12.73%, respectively.…”
Section: Developments In the Precursors And Synthetic Methods For Ani...mentioning
confidence: 99%
“…113 Interestingly, some researchers prepared green CQDs with food as raw material, which fully demonstrated the high biocompatibility of CQDs. 114,115 Nevertheless, although the biocompatibility of CQDs has been reported in many studies, some researchers have found that there is a "threshold" for the low toxicity of CQDs. Liu et al reported the CQDs prepared at high temperature by mixing folic acid and CuCl 2 with anhydrous ethanol.…”
Section: Characterization and Biocompatibility Of Cqdsmentioning
confidence: 99%